Activation of the porcine alveolar macrophages via toll-like receptor 4/NF-κB mediated pathway provides a mechanism of resistin leading to inflammation. (October 2018) - Li, Bi; Fang, Jing; Zuo, Zhicai; Yin, Sirui; He, Tingting; Yang, Mingxian; Deng, Junliang; Shen, Liuhong; Ma, Xiaoping; Yu, Shumin; Wang, Ya; Ren, Zhihua; et al.
Highlights: Resistin is determined as an inflammatory mediator on porcine alveolar macrophages (PAMs). A mechanism of resistin-induced pro-inflammatory effect on PAMs has been clarified and analyzed. Resistin activates PAMs in a TLR4-dependent manner via the activation of NF-κB (TLR4/MyD88/TRAM/NF-κB). Abstract: Resistin, a previously discovered cysteine-rich adipokine known to regulate glucose metabolism, has been emerged as a mediator in inflammation and immunity. Its level was supposed to be related to the expression of indicators, such as interleukin-1β (IL-1β), IL-6 and tumor necrosis factor-α (TNF-α) in inflammation. Toll-like receptor 4 (TLR4) was reported to be a receptor for resistin in cells, like leukocytes and peripheral blood mononuclear cells (PBMC). However, the pro-inflammatory role of resistin and its intracellular mechanisms in alveolar macrophages have not been thoroughly validated. Here we found that the pro-inflammatory cytokine expression in porcine alveolar macrophages (PAMs) was positively correlated with resistin. Our results also showed that resistin induced the expression of TLR4, intracellular molecules myeloid differentiation primary response protein 88 (MyD88), TRIF-related adaptor molecule (TRAM) and nuclear factor κB (NF-κB) in PAMs. In contrast, inhibition of TLR4, MyD88, TRAM and NF-κB abrogated the pro-inflammatory effect of resistin on PAMs. Additionally, the associations among TLR4, MyD88/TRAM and NF-κB were investigated by introducing TLR4-siRNA, MyD88-siRNA and TRAM-siRNA respectively into PAMs prior to the treatment with resistin. Taken together, our findings demonstrated that resistin promoted the production of pro-inflammatory cytokine in PAMs via TLR4/NF-κB-mediated pathway (TLR4/MyD88/TRAM/NF-κB).